A head-to-head comparison of 4-L polyethylene glycol and low-volume solutions before colonoscopy: which is the best? A multicentre, randomized trial - Kojecky, Vladimir; Matous, Jan; Keil, Radan; Dastych, Milan; Kroupa, Radek; Zadorova, Zdena; Varga, Michal; Dolina, Jiri; Kment, Milan; Hep, Aleš (International journal of colorectal disease, 2017)
PURPOSE: The purpose of this study is to compare the efficacy and tolerability of polyethylene glycol (PEG) to sodium picosulfate/magnesium citrate (SPMC) and low-volume polyethylene glycol/ascorbic acid (PEGA) in a single- or split-dose regimen for colonoscopy bowel preparation. METHODS: This was a prospective, randomized, endoscopist-blinded, multicentre study. Outpatients received either PEG or SPMC or PEGA in a single or a split dose before the colonoscopy. Quality and tolerability of the preparation and complaints during preparation were recorded. RESULTS: Nine hundred seventy-three patients were analysed. Satisfactory bowel cleansing (Aronchick score 1 + 2) was more frequent when a split dose was used irrespective of the solution type (PEG 90.1 vs 68.8%, PEGA 86.0 vs 71.6%, SPMC 84.3 vs 60.2%, p < 0.001). SPMC was the best tolerated followed by PEGA (p < 0.006) and PEG as the worst (p < 0.001). Tolerability did not correlate with the regimen and amount of the solution used. Female gender is associated with a higher incidence of nausea, vomiting and pain (p < 0.029). CONCLUSIONS: Both PEG, PEGA and SPMC are fully comparable in terms of colonic cleansing when used in similar regimens. The split-dose preparation is more effective in all agents. SPMC and PEGA are better tolerated than PEG. The preparation regimen and/or the volume do not affect tolerability.
Keywords: Citric Acid; Ascorbic Acid; léčebná irigace; Organometallic Compounds; Female; Picolines; výsledek terapie; ženské pohlaví; Polyethylene Glycols; projímadla; lidé; organokovové sloučeniny; Therapeutic Irrigation; Treatment Outcome; purgativa; kyselina citronová; citráty; polyethylenglykoly; Colonoscopy; prospektivní studie; Male; Prospective Studies; Czech Republic; kyselina askorbová; Cathartics; kolonoskopie; Česká republika; Citrates; Laxatives; pikoliny; mužské pohlaví; Humans